Step-by-step explanation:
Assume length of side 2 = L
Area of parallelogram is Height x L
So, 72 = 8 x L
L = 9
Answer: 14x + 42
7(2x+4)+14
14x + 28 + 14
<u>14x + 42</u>
Step-by-step explanation:
Answer:
4
Step-by-step explanation:
9x=10x-4
x=4
ededededededededededededededededdedededededededededededededededededededededededededededededededededededededededededededededededededededededddeeedddeeedddeeedddeeeddd-------------------------------------------------------------------------------------------------------------------------------------------------------
Answer:
The sum of the first six terms is 38.39
Step-by-step explanation:
This is a geometric sequence since the common difference between each term is ![-\frac{1}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B4%7D)
Thus, ![r=-\frac{1}{4}](https://tex.z-dn.net/?f=r%3D-%5Cfrac%7B1%7D%7B4%7D)
To find the sum of first six terms, we need to find the fifth and sixth term of the sequence.
To find the fifth term:
The general form of geometric sequence is ![a_{n}=a_{1} \cdot r^{n-1}](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7B1%7D%20%5Ccdot%20r%5E%7Bn-1%7D)
To find the fifth term, substitute
in ![a_{n}=a_{1} \cdot r^{n-1}](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7B1%7D%20%5Ccdot%20r%5E%7Bn-1%7D)
![\begin{aligned}a_{5} &=(48) \cdot\left(-\frac{1}{4}\right)^{5-1} \\&=(48) \cdot\left(-\frac{1}{4}\right)^{4} \\&=(48)\left(\frac{1}{256}\right) \\a_{5} &=0.1875\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7Da_%7B5%7D%20%26%3D%2848%29%20%5Ccdot%5Cleft%28-%5Cfrac%7B1%7D%7B4%7D%5Cright%29%5E%7B5-1%7D%20%5C%5C%26%3D%2848%29%20%5Ccdot%5Cleft%28-%5Cfrac%7B1%7D%7B4%7D%5Cright%29%5E%7B4%7D%20%5C%5C%26%3D%2848%29%5Cleft%28%5Cfrac%7B1%7D%7B256%7D%5Cright%29%20%5C%5Ca_%7B5%7D%20%26%3D0.1875%5Cend%7Baligned%7D)
To find the sixth term, substitute
in ![a_{n}=a_{1} \cdot r^{n-1}](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7B1%7D%20%5Ccdot%20r%5E%7Bn-1%7D)
![\begin{aligned}a_{6} &=(48) \cdot\left(-\frac{1}{4}\right)^{6-1} \\&=(48) \cdot\left(-\frac{1}{4}\right)^{5} \\&=(48)\left(-\frac{1}{1024}\right) \\a_{5} &=-0.046875\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7Da_%7B6%7D%20%26%3D%2848%29%20%5Ccdot%5Cleft%28-%5Cfrac%7B1%7D%7B4%7D%5Cright%29%5E%7B6-1%7D%20%5C%5C%26%3D%2848%29%20%5Ccdot%5Cleft%28-%5Cfrac%7B1%7D%7B4%7D%5Cright%29%5E%7B5%7D%20%5C%5C%26%3D%2848%29%5Cleft%28-%5Cfrac%7B1%7D%7B1024%7D%5Cright%29%20%5C%5Ca_%7B5%7D%20%26%3D-0.046875%5Cend%7Baligned%7D)
To find the sum of the first six terms:
The general formula to find Sn for
is ![S_{n}=\frac{a\left(1-r^{n}\right)}{1-r}](https://tex.z-dn.net/?f=S_%7Bn%7D%3D%5Cfrac%7Ba%5Cleft%281-r%5E%7Bn%7D%5Cright%29%7D%7B1-r%7D)
![\begin{aligned}S_{6} &=\frac{48\left(1-\left(-\frac{1}{4}\right)^{6}\right)}{1-\left(-\frac{1}{4}\right)} \\&=\frac{48\left(1-\frac{1}{4096}\right)}{1+\frac{1}{4096}} \\&=\frac{48(0.95)}{5} \\&=\frac{48(0.9998)}{5} \\&=\frac{48(0.9998)}{5} \\&=\frac{47.9904}{5} \\&=38.39\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7DS_%7B6%7D%20%26%3D%5Cfrac%7B48%5Cleft%281-%5Cleft%28-%5Cfrac%7B1%7D%7B4%7D%5Cright%29%5E%7B6%7D%5Cright%29%7D%7B1-%5Cleft%28-%5Cfrac%7B1%7D%7B4%7D%5Cright%29%7D%20%5C%5C%26%3D%5Cfrac%7B48%5Cleft%281-%5Cfrac%7B1%7D%7B4096%7D%5Cright%29%7D%7B1%2B%5Cfrac%7B1%7D%7B4096%7D%7D%20%5C%5C%26%3D%5Cfrac%7B48%280.95%29%7D%7B5%7D%20%5C%5C%26%3D%5Cfrac%7B48%280.9998%29%7D%7B5%7D%20%5C%5C%26%3D%5Cfrac%7B48%280.9998%29%7D%7B5%7D%20%5C%5C%26%3D%5Cfrac%7B47.9904%7D%7B5%7D%20%5C%5C%26%3D38.39%5Cend%7Baligned%7D)
Thus, the sum of first six terms is 38.39